Synergy Between Sustainable Leadership and Stakeholder Management Towards Project Performance (Journal of Asian Development Studies, 2025)
Grounded in stakeholder theory, this study examines the synergy between sustainable leadership and stakeholder management toward project performance. The study's objectives are to provide empirical evidence supporting the significance of sustainable leadership and stakeholder management in enhancing project performance. To achieve these objectives, cross-sectional data from construction project managers and professionals (N = 320) have been collected through a self-administered survey questionnaire. PLS-SEM has been applied for hypothesis testing using SmartPLS. The results verify that the positive relationship between sustainable leadership and project success is direct and indirect via effective stakeholder management. Additionally, these results indicate that stakeholder management mediates the relationship between leadership and stakeholder engagement, such that strong leadership promotes greater stakeholder engagement, resulting in superior project outcomes. The findings offer practical and managerial implications to project managers and policymakers in enhancing project performance through sustainable leadership and stakeholder management.